Effect Of Land Use And Land Cover (Lulc) And Anthropogenic Activities On Kinta River Water Quality - Yaakub, Azyana (2013)
Research was carried out to assess the relationship between land use and water quality of Kinta River. The objectives of this research were to identify the possible pollution sources influencing the water quality, to determine the influence of land use and cover within zones of specific radii and entire catchment area on river water quality and to investigate the best land use predictor for the prediction of river water quality. Sixty locations were identified across the Kinta catchment area as possible pollution sources and had been analyzed with one-way ANOVA. These 60 locations were related to various anthropogenic activities such as industries, residential areas, wet markets etc. Ten sampling points (PT 1 to PT 10) of Pari River tributaries were selected and 90 water samples were taken from these points using grab water sampling method. The percentage of land use of five predictor variables specifically forest land, agricultural land, developed area, mining area and water bodies were extracted from the entire catchment area and buffer zone using Arc View 9.3 Data Processing. Statistical analysis was conducted against 12 water quality parameters; temperature, dissolved oxygen (DO), conductivity, salinity, total dissolved solids (TDS), pH, chemical oxygen demand (COD), turbidity, nitrate, phosphate, biochemical oxygen demand (BOD) and suspended solids (SS). It was obvious that the industrial areas recorded on the average the highest levels of any one of the 12 parameters.